CYTOLOGICAL SCREENING FOR CERVICAL CANCER DIAGNOSING - Светлана Ивановна Елгина; Ольга Сергеевна Золоторевская; Игорь Сергеевич Захаров; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Виктория Анатольевна Разумова; Алексей Юрьевич Кратовский (The Publishing House Medicine and Enlightenment, 2019)
Objective - to study the advantages of liquid-based cytology in comparison with Pap test in early diagnosis of cervical cancer. Materials and methods. The clinical records of 145 women of reproductive age were analysed. The women had applied to antenatal clinic in Clinical Policlinic N 20 were studied by clinical, laboratory, statistical methods. All women underwent cytological screening both with a technology such as the PAP test and a liquid-based one. Results. While estimating sensitivity, specificity and prognostic value of the cytological screening, the following findings were received: The sensitivity of liquid-based cytology was 70.0 % while that of the Pap test - 60.0 %. The specificity of liquid-based cytology (86.0 %) was lower than that of the PAP test (88.0 %). The prognostic value of the positive result of the liquid-based cytology test (75.0 %) was identical to the PAP test (87.0 %) prognostic value. However, the prognostic value of the negative result of the liquid-based cytology test (83.0 %) was much higher than that of the PAP test (50.0 %). Conclusion: We identified that both screenings have similar prediction value for disease probability. However liquid-based cytology test allows reducing the number of negative results. Currently a wide application of more efficient methods - detection of Human Papilloma Virus DNA of high oncogenic risk - is required for the well-arranged screening program.